A generalized Combinatorial Nullstellensatz for multisets. (January 2020) - Batzaya, Gantsooj; Bayarmagnai, Gombodorj
Abstract: The Combinatorial Nullstellensatz is one of the most powerful algebraic tools in combinatorics. The aim of this paper is to prove an extension of the Combinatorial Nullstellensatz for multisets due to Kós–Rónyai. Our generalization gives an improvement on the size of sets chosen in the statement of Combinatorial Nullstellensatz for some polynomials.